2004
DOI: 10.1177/104063870401600302
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Infection in Free-Ranging Squirrels in Illinois

Abstract: Abstract. West Nile virus (WNV) infection was diagnosed in 13 gray squirrels (Sciurus carolinensis) and 3 fox squirrels (Sciurus niger) that were observed with neurologic signs before death or found dead. All 16 had gliosis throughout all sections of the brain. Most had lymphoplasmacytic encephalitis or meningoencephalitis, many with admixed neutrophils. Neuronal necrosis and neuronophagia were also prominent features. West Nile virus antigen was demonstrated in the brain, spleen, heart or kidney in 10 of 13 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…The absence of gross lesions in symptomatic and asymptomatic WNV-infected gray and/or fox squirrels, and presence of lymphoplasmacytic inflammatory lesions in brain, kidney, and liver tissues are consistent with observations in experimentally infected (Root et al 2006) or naturally infected symptomatic or dead squirrels (Kiupel et al 2003, Heinz-Taheny et al 2004.…”
Section: West Nile Virus and Fox Squirrels 231supporting
confidence: 85%
See 2 more Smart Citations
“…The absence of gross lesions in symptomatic and asymptomatic WNV-infected gray and/or fox squirrels, and presence of lymphoplasmacytic inflammatory lesions in brain, kidney, and liver tissues are consistent with observations in experimentally infected (Root et al 2006) or naturally infected symptomatic or dead squirrels (Kiupel et al 2003, Heinz-Taheny et al 2004.…”
Section: West Nile Virus and Fox Squirrels 231supporting
confidence: 85%
“…Similarly, Root et al (2006) reported that none of 12 viremic squirrels that were maintained experimentally for 12 days developed symptoms of disease. Symptoms of the affected squirrel were similar to those observed in naturally infected fox and gray squirrels: incoordination, tremors, and varying degrees of paralysis (Kiupel et al 2003, Heinz-Taheny et al 2004, Padgett et al 2007. Although squirrel no.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, infected mice were euthanized in the acute phase of infection when they began to show clinical signs; as wild prey items, these infected rodents would be relatively easy prey for raptors. The predatory nature of raptors, along with reports of WNV-positive mammals (e.g., Heinz-Taheny et al, 2004), establish the possibility of oral infection in some free-ranging raptors through consumption of infected prey.…”
Section: Discussionmentioning
confidence: 95%
“…Mosquitoes are the primary vectors for WNV, and wild birds are the principal hosts (Hubalek and Halouzka, 1999;Campbell et al, 2002;McLean et al, 2002). Evidence of WNV infections in a variety of vertebrates (Steele et al, 2000;Komar et al, 2001;Ludwig et al, 2002;Lichtensteiger et al, 2003;Steinman et al, 2003;Heinz-Taheny et al, 2004) suggests that WNV is widespread in wildlife, and other vertebrate hosts might serve as an overwintering and maintenance reservoir for WNV.…”
mentioning
confidence: 99%